2009
DOI: 10.1155/2009/936541
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Cr(VI) from Aqueous Solution Using Modified Pomegranate Peel : Equilibrium and Kinetic Studies

Abstract: The present investigation deals with the utilization of modified pomegrenate peel (MPGP) and formaldehyde modified pomegrenate peel (FMPGP) as adsorbents for the removal of chromium Cr(VI) from aqueous solution. A series of experiments were conducted in a batch system to evaluate the effect of system variables. The effect of pH, initial Cr(VI) concentration, contact time, adsorbent dosage and temperature were considered. The optimal pH values of Cr(VI) removal by MPGP and FMPGP were 2.0 and 3.0 respectively. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 22 publications
1
17
0
Order By: Relevance
“…This could probably be due to the ratio of mass of adsorbent to concentration of the adsorbate. Similar results have been observed by [21], [22] and [23].…”
Section: Figure 3: Effect Of Initial Concentration Of Pb (Ii) Ions Onsupporting
confidence: 92%
“…This could probably be due to the ratio of mass of adsorbent to concentration of the adsorbate. Similar results have been observed by [21], [22] and [23].…”
Section: Figure 3: Effect Of Initial Concentration Of Pb (Ii) Ions Onsupporting
confidence: 92%
“…Few studies have been reported on the application of PGP for removal of different HMs from water samples. Peels were used as such (untreated) or after modification (chemically or thermally) [16][17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Pomegranate peels are rich in tannins [34][35][36]. They have been used traditionally for their medicinal properties as anticancer, anti-inflammatory, antioxidant and antithelminthic [37,38] and for other purposes such as tanning, dyeing [39,40] and heavy metal removal [41]. Pomegranate peels are characterized by an interior network of membranes comprising almost 26-30% of total fruit weight and are characterized by substantial amounts of phenolic compounds, including flavonoids (anthocyanins, catechins and other complex flavonoids) and hydrolysable tannins (punicalin, pedunculagin, punicalagin, gallic and ellagic acid) [42][43][44].…”
Section: Pomegranatementioning
confidence: 99%